Алдановский образ русских идей в произведении Ульмская ночь - Biełousowa, Wiera (Acta Polono-Ruthenica, 2006)
In the article analyzed is the notion of Mark Aldanow concerning the Russian idea presented In the philosophical treatise entiled Ulmska noc.